HOTS Study: How are the literacy and thinking skills of students different? - Kurniawan, Dwi Agus; Darmaji, Darmaji; Astalini, Astalini; Widodo, Rido Ilham (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2022)
This research was conducted to determine how the influence of digital literacy and critical thinking skills. This research was conducted using a mixed method with the convergent parallel design. The subjects of this study were students from SMAN 6 Batanghari and SMAN 10 Batanghari with a specialization in science, where each school took 2 classes with a total of 80 students as samples with 297 eleventh graders in both schools as population, where research sample chosen with purposive sampling. The data analysis carried out in this study was a normality test, linearity test, and regression test. From this research, it was found that there were significant differences in the level of digital literacy skills and understanding of students on digital literacy between the two test schools. Significant differences are also seen in the level of critical thinking of students. The interesting thing in the findings of this research is that students who have a good level of skills and understanding of digital literacy will have a good level of critical thinking as well. So, it was found that digital literacy also has an influence on students' critical thinking skills.